2018
DOI: 10.1097/bpo.0000000000001211
|View full text |Cite
|
Sign up to set email alerts
|

Amputation Outcomes in Congenital Pseudarthrosis of the Tibia

Abstract: Level IV-case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
6
0
6
Order By: Relevance
“…Some researchers believe that the involved tibia in patients should be amputated early to preserve extremity function with an adequate prosthesis because the residual deformities impair the affected lower-extremity walking function. 16 One of the typical residual deformities was tibial malalignment in the frontal plane, which includes proximal tibial valgus and ankle valgus deformities and tibial diaphyseal angulation. To address this rather intractable problem, Charnley 17 first reported that using an IMR to transfix the talus and calcaneus successfully treated two cases of CPT in 1956, demonstrating that an IMR can maintain the involved tibial alignment and turn abnormal angulation strains into longitudinal compression forces to reduce the possibility of refracture occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers believe that the involved tibia in patients should be amputated early to preserve extremity function with an adequate prosthesis because the residual deformities impair the affected lower-extremity walking function. 16 One of the typical residual deformities was tibial malalignment in the frontal plane, which includes proximal tibial valgus and ankle valgus deformities and tibial diaphyseal angulation. To address this rather intractable problem, Charnley 17 first reported that using an IMR to transfix the talus and calcaneus successfully treated two cases of CPT in 1956, demonstrating that an IMR can maintain the involved tibial alignment and turn abnormal angulation strains into longitudinal compression forces to reduce the possibility of refracture occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Neurofibromatous osteopathy is one of the most challenging conditions for pediatric orthopedic surgeons, and many operations will be required for successful treatment. [7] Currently, most patients are treated by excising the lesions, stabilizing the fragments with internal or external fixation, and bone grafting. In addition to this basic approach, some surgeons advocate the local administration of bone morphogenetic protein, [8,9] periosteal grafting, [10] and vascularized fibular grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Neurofibromas that are occasionally extending in large areas of the tibia, is difficult to be surgically removed. In these cases, amputation of the limb and use of prosthesis can be proposed [45,46].…”
Section: Osseous Involvement Of Long Bones 31 Tibiamentioning
confidence: 99%